2015
DOI: 10.1016/j.nima.2014.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Neutron detector based on Particles of 6Li glass scintillator dispersed in organic lightguide matrix

Abstract: Q3detectors 6 Li glass Neutron/gamma separation 3 He replacement Nuclear safeguards Neutron coincidence counters Active interrogation a b s t r a c t Most 3 He replacement neutron detector technologies today have overlapping neutron-gamma pulseheight distributions, which limits their usefulness and performance. Different techniques are used to mitigate this shortcoming, including Pulse Shape Discrimination (PSD) or threshold settings that suppress all gammas as well as much of the neutrons. As a result, count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…[7]). Alternative matrices, such as nonscintillating acrylic, may also yield composite, lithium-glass-based detectors with very effective neutron/γ discrimination: Ianakiev et al have shown promising initial results for high neutron/γ discrimination efficacy with composites based on GS20-type lithium glass and poly(methyl methacrylate) (PMMA) or mineral oil matrices [29].…”
Section: Discussionmentioning
confidence: 99%
“…[7]). Alternative matrices, such as nonscintillating acrylic, may also yield composite, lithium-glass-based detectors with very effective neutron/γ discrimination: Ianakiev et al have shown promising initial results for high neutron/γ discrimination efficacy with composites based on GS20-type lithium glass and poly(methyl methacrylate) (PMMA) or mineral oil matrices [29].…”
Section: Discussionmentioning
confidence: 99%
“…A new detector concept for 3 He replacement based on GS20 6 Li scintillator glass particles uniformly distributed in mineral oil that serves as both light transport and neutron moderation medium has recently been developed at LANL. The technology provides good neutron/gamma-ray separation by selection of a scintillator particle size that limits the energy deposited by gamma-rays to below the peak of the 6 Li reaction products [Ianakiev 2014a]. A prototype detector with an active volume of 7.6 cm diameter by 25.4 cm length containing ~2.7 vol% of GS20 glass scintillator was developed and is shown in Figure 3.25.…”
Section: Neutron Detector Based On Particles Of 6 LI Glass Scintillatormentioning
confidence: 99%
“…The neutron detection technique is one of the key issues in neutron research. The widespread 3 He-based detectors are becoming less available due to constraints in gas supply. Alternative types of detectors are required that can provide reasonable detection efficiency for neutrons in a wide energy range, a limited sensitivity to γ rays or ability to discriminate them, and a short dead time.…”
Section: Introductionmentioning
confidence: 99%
“…Works on reducing the γ-ray sensitivity of glass scintillators are underway in two main directions. The first direction is to create heterogeneous scintillators based on lithium glasses with various geometries and optical characteristics, in particular, for problems of control over nuclear-material handling [3][4][5]. The second direction is to search for methods of digital signal processing to discriminate between pulses from neutrons and γ rays [6,7].…”
Section: Introductionmentioning
confidence: 99%